FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK HIDUP BERSIH DAN SEHAT SEBAGAI UPAYA PENCEGAHAN DEMAM TIFOID PADA SISWA DI SDN GENUKSARI 02 SEMARANG - Tutut Dwi Adi Cahyani; Syamsulhadi Budi Musthofa; Bagoes Widjanarko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Typhoid fever is an acute infection of the digestive tract caused by Salmonella typhi. Riskesdas Report in 2007, stated that prevalence of typhoid fever in Central Java province was 1.61%. In Semarang, densely population areas with high potential for typhoid fever for children 4-15 years old are Genuk district with number of percentage 9.8% and noticed as top three in Semarang in 2016. Recent studies in Southeast Asia showed the highest incidence occurring in children due to hygiene factors where it is closely related to the Practice of Clean and Healthy Life. This research aimed to determine the factors that correlated with the practice of clean and healthy life as prevention of typhoid fever for students in primary school of Genuksari 02 Semarang.The type of this research is descriptive analytic with quantitative approach. The sample in this research using total sampling for all students of 5th grade in Primary School of Genuksari 02 who had never suffered typhoid fever with amount 60. The data was collected by interview using questionnaire. This research use univariate and bivariate analysis. The research showed that most of respondents are 11 years old 53.3%, female genders are 51.7%. 61.7% of respondents have good practice of clean and healthy life. Variables that related with practice of clean and healthy life are Knowledge (p = 0,006) and facility of infrastructure (p = 0,005).While the unrelated variables are age of respondent (p=0,907), gender (p=0,876), Attitude (p=0,114), and environmental support (p=0,936).This research is expected to be an input to improve learning about CHLB in order to prevent typhoid fever in school-age children, especially primary school.